PENGARUH LITERASI KEUANGAN, PENDAPATAN, MODAL MINIMAL, DAN PENGETAHUAN INVESTASI TERHADAP KEPUTUSAN INVESTASI KARYAWAN: (Studi Kasus pada Karyawan di Kantor Perpajakan) - Ameliya Dian Pratiwi; Ika Indriasari; Rita Meiriyanti (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2023)
The importance of understanding financial and investment aspects for employees, especially in the tax sector, is highlighted in the context of making smart financial decisions. In this context, financial literacy, income, minimum capital, and investment knowledge are crucial factors that may influence employees' investment decisions. This study aims to test and analyze the effect of financial literacy, income, minimal capital, and investment knowledge of employee investment decisions. The sample in this study was 99 sumatran taxation employees who were calculated using the slovin formula. In this study used the quantitative method with sampling technique in this study using a Probability Sampling with a Simple Random Sampling approach. This study uses multiple linear regression analysis and classic assumption tests. The results of this study show that there is no influence between the financial literacy variable on employee investment decisions, the income variable has a positive and significant influence on employee investment decisions, there is no influence between the minimum capital variable on employee investment decisions, and investment knowledge which has a positive and significant influence. significant impact on employee investment decisions.